2013
DOI: 10.1371/journal.pone.0070991
|View full text |Cite
|
Sign up to set email alerts
|

Zileuton Improves Memory Deficits, Amyloid and Tau Pathology in a Mouse Model of Alzheimer’s Disease with Plaques and Tangles

Abstract: The 5-lipoxygenase (5LO) enzyme is widely distributed within the central nervous system. Previous works showed that this protein is up-regulated in Alzheimer’s disease (AD), and plays an active role in the development of brain amyloidosis in the APP transgenic mice. In the present paper, we studied the effect of its pharmacological inhibition on the entire AD-like phenotype of a mouse model with plaques and tangles, the 3×Tg mice. Compared with mice receiving placebo, the group treated with zileuton, a specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 19 publications
1
43
0
Order By: Relevance
“…The dose of the drug selected in this study was based on our previous work, showing that this concentration of drug significantly reduces 5LO activation (Chu et al., 2013). As shown in Figure 2, no significant differences were observed between the P301S control group and P301S mice receiving zileuton when steady‐state levels of brain 5LO protein were assayed.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The dose of the drug selected in this study was based on our previous work, showing that this concentration of drug significantly reduces 5LO activation (Chu et al., 2013). As shown in Figure 2, no significant differences were observed between the P301S control group and P301S mice receiving zileuton when steady‐state levels of brain 5LO protein were assayed.…”
Section: Resultsmentioning
confidence: 99%
“…In our study, mice were exposed to the drug ad libitum as it was dissolved in their drinking water, and based on the daily consumption of water of approximately 5 ml, we were confident that, as in our previous studies, they were exposed to a therapeutic dose of zileuton (Chu et al., 2013). To confirm compliance with the treatment as well as target engagement, we assessed brain levels of LTB4, the major metabolic product of 5LO enzymatic activation, and found that indeed it was reduced by almost 80%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…But the use of 5-LOX inhibitors demonstrated that 5-LOX and its products have a stronger impact on Aβ peptide production and tau phosphorylation in neuronal cells 37 than in the proliferation of glial cells and neuroinflammation.…”
mentioning
confidence: 99%